Histidine‐rich glycoprotein augments natural killer cell function by modulating PD‐1 expression via CLEC‐1B. Issue 3 (22nd May 2019) - Nishimura, Yoshito; Wake, Hidenori; Teshigawara, Kiyoshi; Wang, Dengli; Sakaguchi, Masakiyo; Otsuka, Fumio; Nishibori, Masahiro
Abstract: Augmentation of natural killer (NK) cell cytotoxicity is one of the greatest challenges for cancer immunotherapy. Although histidine‐rich glycoprotein (HRG), a 75‐kDa glycoprotein with various immunomodulatory activities, reportedly elicits antitumor immunity, its effect on NK cell cytotoxicity is unclear. We assessed NK cell cytotoxicity against K562 cells. We also measured concentrations of cytokines and granzyme B in the cell supernatant. The proportion of CD56 bright NK cells and NK cell surface PD‐1 expression was assessed with flow cytometry. The neutralizing effects of anti‐C‐type lectin‐like receptor (CLEC) 1B against HRG were also measured. NK cell morphological changes were analyzed via confocal microscopy. HRG significantly increased NK cell cytotoxicity against K562 cell lines. HRG also increased the release of granzyme B and the proportion of CD56 bright NK cells. Further, HRG was able to decrease NK cell surface PD‐1 expression. The effects of HRG on NK cells were reversed with anti‐CLEC‐1B antibodies. Additionally, we confirmed NK cell nuclear morphology and F‐actin distribution, which are involved in the regulation of cytotoxic granule secretion. Because both PD‐1 and CLEC‐1B are associated with prognosis during malignancy, HRG incorporates these molecules to exert the antitumor immunity role. These facts indicate the potential of HRG to be a new target for cancer immunotherapy.